POLQ plays a key role in the repair of CRISPR/Cas9‐induced double‐stranded breaks in the moss Physcomitrella patens. Issue 3 (5th February 2019) - Mara, Kostlend; Charlot, Florence; Guyon‐Debast, Anouchka; Schaefer, Didier G.; Collonnier, Cécile; Grelon, Mathilde; Nogué, Fabien
Summary: Double‐stranded breaks can be repaired by different mechanisms such as homologous recombination (HR), classical nonhomologous end joining (C‐NHEJ) and alternative end joining (Alt‐EJ). Polymerase Q (POLQ) has been proposed to be the main factor involved in Alt‐EJ‐mediated DNA repair. Here we describe the role of POLQ in DNA repair and gene targeting in Physcomitrella patens . The disruption of the POLQ gene does not influence the genetic stability of P. patens nor its development. The polq mutant shows the same sensitivity as wild‐type towards most of the genotoxic agents tested (ultraviolet (UV), methyl methanesulfonate (MMS) and cisplatin) with the notable exception of bleomycin for which it shows less sensitivity than the wild‐type. Furthermore, we show that POLQ is involved in the repair of CRISPR‐Cas9‐induced double‐stranded breaks in P. patens . We also demonstrate that POLQ is a potential competitor and/or inhibitor of the HR repair pathway. This finding has a consequence in terms of genetic engineering, as in the absence of POLQ the frequency of gene targeting is significantly increased and the number of clean two‐sided HR‐mediated insertions is enhanced. Therefore, the control of POLQ activity in plants could be a useful strategy to optimize the tools of genome engineering for plant breeding.